Family affair - Oliver, Fiz; Williams, Margaret; Fisher, Paul; Milne, Paula; Longman (Firm) ([S.l.] : Longman ELT Video, 1984)
After her divorce, Anna lives with her son Terry, who encourages her to meet new friends. However, Alan, her ex-husband manages to make Anna distrust Jeff, a new-found friend
Cassette 1 : Units 1 - 6 (13 mins.), cassette 2 : Units 7 - 15 (13 mins.)
Intended audience : Students of English at intermediate level
Photographer, Barry Noakes, ; editor, Paul Davies ; music, Robert Lockhart
Cast : Carrol Drinkwater, Bill Nighy, Chris Chescoe
Keywords: English language -- Study and teaching (Secondary)